O potrzebie wspomagania rozwoju małego dziecka. Wyzwania dla praktyki pedagogicznej - Ratajczak, Anna (Studia Edukacyjne, 2018)
The subject of the article is the concept of supporting the development of a small child, as this action, which taken by significant people, can significantly contribute to the optimization of development. The article consists of three main issues. In the first of them, the concept of development support will be subject to the characteristics. Subsequently, selected results of own research will be presented, and ultimately the author will attempt to indicate specific implications for pedagogical practice related to the topic being undertaken.